2001
DOI: 10.1046/j.1464-6722.2001.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endo‐polygalacturonase activities of citrus and non‐citrus races of Geotrichum candidum, and cloning and expression of the corresponding genes

Abstract: summary Geotrichum candidum citrus race, a fungus that causes a sour rot disease in citrus fruits, secretes an endo-polygalacturonase (PG) that may facilitate the disease. There also exists a non-citrus race that is non-pathogenic to citrus fruits. In this research, we found that the PG activity of the citrus race isolates was much higher than that of the non-citrus race isolates in culture medium and inoculated lemon peel, and that there was a significant correlation between the PG activity and pathogenicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Results suggested that the higher initial amount of enzyme produced in vivo by the citrus race and the higher sensitivity of the pectin in situ to this enzyme were the two main factors governing the unique virulence of the citrus race on citrus fruits (51). A later manuscript by Nakamura et al (73) showed 68% identity at the amino acid level between endo-PG from citrus and noncitrus races, suggesting that the two enzymes are similar but not identical. It could be hypothesized that the endo-PG of the citrus race can efficiently degrade the protopectin in citrus fruits (water-insoluble pectic sustenance present in intact tissue), whereas the noncitrus race cannot.…”
Section: The Role Of Pectic Enzymes In Soft-rot Decays Of Citrusmentioning
confidence: 99%
“…Results suggested that the higher initial amount of enzyme produced in vivo by the citrus race and the higher sensitivity of the pectin in situ to this enzyme were the two main factors governing the unique virulence of the citrus race on citrus fruits (51). A later manuscript by Nakamura et al (73) showed 68% identity at the amino acid level between endo-PG from citrus and noncitrus races, suggesting that the two enzymes are similar but not identical. It could be hypothesized that the endo-PG of the citrus race can efficiently degrade the protopectin in citrus fruits (water-insoluble pectic sustenance present in intact tissue), whereas the noncitrus race cannot.…”
Section: The Role Of Pectic Enzymes In Soft-rot Decays Of Citrusmentioning
confidence: 99%
“…Previously, we isolated three PG genes from G. candidum, S31pg1 (AB099408) and S31pg2 (AB0994089) from pathogenic isolate S3 and S63pg1 (AB062511) from nonpathogenic isolate S63 (Nakamura et al 2001(Nakamura et al , 2003. Using PGs expressed by a yeast expression system, we clarified that S31PG1 was important in pathogenicity in lemon fruit, but S31PG2 was not (Nakamura et al 2003).…”
mentioning
confidence: 94%
“…We previously isolated a PG gene, S31pg1, cDNA from G. candidum citrus race S31 (Nakamura et al 2001). S31pg1 was expressed in both cultures and lemon fruit infected with the citrus race S31: The gene was not catabolite-repressed (Nakamura et al 2001).…”
Section: Introductionmentioning
confidence: 99%